2022
DOI: 10.1039/d2cp05062e
|View full text |Cite
|
Sign up to set email alerts
|

Emission modulation of fluorescent turn-on mode dibenzothienyl sulfonyl ethene photoswitches embedded in a polymer film

Abstract: Since decades photochromic molecules have attracted attention for their potential of using light as external stimulus to change their photophysical properties. Here we report the spectroscopic characterization of two emissive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…52 Koḧler and co-workers recently reported a study on photoswitchable molecules derived from the diarylethene group as shown in Figure 4b. 50 Such molecules undergo center ring-closing and ring-opening reactions upon illumination with 325 or 420 nm light. The ring reconfiguration changes lead to changes in both the absorption and emission spectra of the molecules.…”
Section: ■ Single Nanoparticle Epdmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Koḧler and co-workers recently reported a study on photoswitchable molecules derived from the diarylethene group as shown in Figure 4b. 50 Such molecules undergo center ring-closing and ring-opening reactions upon illumination with 325 or 420 nm light. The ring reconfiguration changes lead to changes in both the absorption and emission spectra of the molecules.…”
Section: ■ Single Nanoparticle Epdmentioning
confidence: 99%
“…(b) Optical modulation of the emission intensity of photoswitchable molecules. Adapted with permission from ref . Copyright 2022 The Royal Society of Chemistry.…”
Section: Applications and Directionsmentioning
confidence: 99%
See 1 more Smart Citation